Bridging perspectives: Key insights from a gender & youth integration learning event - Kayamba-Phiri, Fundi (International Food Policy Research Institute, 2023)
In light of the need to learn from and collaborate with other USAID implementing partners on effectively addressing the issues that affect women and youth in their programming, Titukulane organized a focused event in September 2022. Prioritizing the engagement of women and youth in all development activities has immense importance and needs more emphasis. This is particularly true for projects that aim to create lasting impact and positive change in communities. Titukulane, through USAID's Bureau for Humanitarian Assistance, organized a collaborative meeting with USAID Implementing Partners in Malawi. Through this effort, the implementing partners identified potential areas for integration and collaboration that can further enhance the impact of development programs.